Is Critical Thinking Particularly Necessary when Using Augmented Reality in Knowledge Society? An Introductory Paradox - Ariso Salgado, José María (Augmented Reality: Reflections on Its Contribution to Knowledge Formation, 2023)
The growth of Information and CommunicationTechnology has delivered such a vast amount of information that the term ‘information society’ was created to refer to a society characterized, above all, by the global and massive scalein which raw data are created and disseminated. But the mere fact of receiving information must not be confused with knowledge creation.
Keywords: critical thinking; augmented reality; knowledge society; Scopus(2)